2020
DOI: 10.3390/plants9081007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Harvest-Aids on Seed Nutrition in Soybean under Midsouth USA Conditions

Abstract: Interest in using harvest aids (defoliants or crop desiccants) such as paraquat, carfentrazone-ethyl, glyphosate, and sodium chlorate (NaClO3) have become increasingly important to assure harvest efficiency, producer profit, and to maintain seed quality. However, information on the effects of harvest aids on seed nutrition (composition) (protein, oil, fatty acids, sugars, and amino acids) in soybean is very limited. The objective of this research was to investigate the influence of harvest aids on seed protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 38 publications
3
13
2
1
Order By: Relevance
“…(2020), but both raffinose and stachyose increased, disagreeing with the results of Bellaloui et al. (2020). The disagreement of the findings could be due to differences in paraquat rates used, cultivars, planting dates, or locations (Valentine et al., 2017), as well as the amount and pattern of rainfall and heat in each year (Bellaloui et al., 2020) as biotic and abiotic factors can increase the severity and the stress response to paraquat.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…(2020), but both raffinose and stachyose increased, disagreeing with the results of Bellaloui et al. (2020). The disagreement of the findings could be due to differences in paraquat rates used, cultivars, planting dates, or locations (Valentine et al., 2017), as well as the amount and pattern of rainfall and heat in each year (Bellaloui et al., 2020) as biotic and abiotic factors can increase the severity and the stress response to paraquat.…”
Section: Discussioncontrasting
confidence: 65%
“…Our results showed that sucrose decreased, agreeing with the results of Bellaloui et al. (2020), but both raffinose and stachyose increased, disagreeing with the results of Bellaloui et al. (2020).…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations